Multifunctional character of agriculture: differences in views between the countries - Lankoski, Jussi; Miettinen, Antti (Maatalouden taloudellinen tutkimuslaitos, 2000)
The paper examines the differences between the developed countries in their attitude towards multifunctional agriculture, non-trade concerns and appropriate policy response for addressing multifunctional agriculture and non-trade concerns. The basic differences between the developed countries stem from the potential gains and losses countries face when agricultural trade is further liberalised. The proponents of multifunctionality fear that further liberalised trade reduces their ability to address non-trade concerns and multifunctional agriculture effectively, whereas export-oriented countries see multifunctionality as an excuse for retaining agricultural supports which may result in reduced export opportunities for them. There is a broad consensus among the WTO members that non-trade concerns such as food security, environmental issues, viability of rural areas and food safety are legitimate concerns, which have to be considered when agricultural trade is further liberalised. The concept of multifunctional agriculture, which covers many of the agriculture-related non-trade concerns, has raised conflicting views among the WTO members. Moreover, countries disagree on appropriate policy responses for sustaining and enhancing the multifunctional character of agriculture. The green box policies are the single most widely supported measures for addressing non-trade concerns and multifunctional agriculture. For the Cairns Group and the United States the green box policies represent effective and universal means, whereas for countries with higher production costs they may not be sufficient to sustain the multifunctional character of agriculture, especially in marginal areas. Thus, the high-cost countries are stressing the need to expand the green box to contain some production-linked support in order to address their non-trade concerns effectively.
Keywords: Ma; tuotannosta irrotettu tuki; vihreä laatikko; monivaikutteisuus; ei-kaupalliset kysymykset; tuotantoon sidottu tuki; decoupled support; green box; multifunctionality; non-trade concerns; production-linked support